High School Extracurricular Program Design: An Effort to Face the Challenges of Contemporary Thinking in Indonesia - Ulil Amri Syafri; Irfan Wahyu Syifa; Endin Mujahidin; Rahendra Maya (Universitas Darussalam Gontor, 2022)
This article aimed to design an extracurricular program in the field of Islamic thought for the high school (SMA) level in Indonesia. This design is in order to face the challenges of thinking from the West. The program is very urgent ‎because these challenges also have an impact on Muslim youth, who are ‎looking for an identity. The research focuses on the educational curriculum at Pesantren At-Taqwa Depok. Where this object is used as a reference for compiling and formulating the design of extracurricular programs in the field of Islamic thought at the (SMA) level. This research is qualitative research with primary data sources obtained from interviews and field observations (field research). The data is used to analyze and describe educational programs and curricula at Pesantren At-Taqwa Depok. The results of the study found that the extracurricular design in the field of thought was based on the concept of al-Tawâssut wa al-'Itidâl and the concept of Ashlaḥa wa 'Mua'shirah. The extracurricular program in the field of thought aimed to produce superior adabi people, broad-minded about Islam and in accordance with the Islamic worldview. This program is actualized in two forms, the first being organizers or forums for developing student potential in a field of thought called the Student-Insight Development Forum. Second, they are programs and activities, such as book sharing, book studies and thematic studies.